PERSEPSI DAN SIKAP MASYARAKAT LOKAL TERHADAP HUTAN DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Masria, Masria; Golar, Golar; Ihsan, Moh. (Jurnal Warta Rimba, 2015)
Forests for people is not new, especially for people who still have the values and traditional culture. Since immemorial time, they do not just see it as a only potential resource, but at the same time it going give shelter for them. Even though, parts of traditional societies is assured that the forest has a spiritual value that is believe that the forest or biotic and abiotic components in it as an object which has a strength and/or supernatural messages they obey. The purpose of this study was to identify the perceptions and attitudes of local people towards the forest. Usefulness expected in this study in order to give information for stakeholders and the public in general. This research employed descriptive methods, through the steps of collecting primary data and secondary data where the data obtained from interviews with respondents and other supporting data such as data from the village government and literature review, using the scaling 1-3-5 (Likert Modification), which would be associated with the conclusions how far the perceptions and attitudes of local people towards forest in the village of Labuan Toposo. Based on the likes scale analysis of public perception of forest might be categorized a quite well. However, despite the good public perception of forest did not insure the occurrence of a positive attitude, even otherwise negative. There are several factors that affect the level of perception, such as education level. Illegal logging activities by part of society could be one of the triggers forest destruction and the occurrence of floods and droughts. Keywords : attitudes, forest, local, communitity, perceptions.